A Magyar Mezőgazdaság folyóirat témaszerkezetének vizsgálata: Médiakutatás a tartalomelemzés módszerével - Móré, Mariann (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Hungary's most important agricultural, output-political weekly journal is the Hungarian Agriculture (original title: Magyar Mezőgazdaság). The first issue was published in 1946 with the purpose of helping the working peasantry's development. I analyzed the articles between 1956 and 2005. According to the principle of content analysis, I limited the number of articles with consideration. I analyzed the articles about harvesting and gathering. It was altogether 171 articles. In all of the 12 categories, there is a high frequency of the topics of quality and workforce. In the articles dealing with harvesting and gathering, there is a high frequency of terms and ideas about quantity and weather. The Hungarian Agriculture considers politics and the life-situation or living standard of the people living on agriculture to be important. But it does not consider issues of scarcity or abundance to be important. The people's personal relationship is also not important, at least according to the analyzed paper.